Trace level determination of beryllium in natural and flavored mineral waters after pre-concentration using activated carbon - Kilinc, Ersin; Bakirdere, Sezgin; Yaman, Mehmet (Taylor & Francis Ltd, 2011)
The concentrations of beryllium (Be) in natural and flavored mineral water samples were determined by flame atomic absorption spectrophotometer (FAAS) after pre-concentration based on the complexation of Be(+2) with a mixture of acetylacetone (pentane-2,4-dione) plus morin (3,5,7,2',4'-pentaoxyflavone) and adsorption on activated carbon. The adsorbed complex was eluted with 1.5 ml of 2.0 M HNO(3) and evaporated to dryness. After adding 1.5 ml of 2 M HNO(3) and centrifuging, Be in acid solution was determined by FAAS. To remove a number of metals present in water, EDTA was used as a chelating agent. Beryllium in mineral water samples was pre-concentrated by 500-fold, taking 750 ml as initial sample and 1.5 ml as the final volume. The relative standard deviations were sufficiently low for practical purposes and recoveries were up to 85%. Spiking experiments were performed in real samples to establish accuracy and recoveries. The limits of detection and quantification were 0.01 and 0.03 ng ml(-1), respectively. Twenty samples were analyzed for their beryllium content using optimum parameters. The highest concentration of beryllium was found to be 0.94 +/- 0.15 ng ml(-1) in a natural mineral water, while beryllium was not detected in five samples.
Keywords: extraction; FAAS; toxic metals; trace elements; metal analysis; beverages; water